Experimental Approaches to the Assessment of Potential Cardioprotective Means with Doxorubicin-Associated Cardiomyopathy - Danilenko, Lyudmila M. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: At present, doxorubicin (DOX) is the most popular anthracycline antibiotic in oncology. The search for substances with a cardiotropic effect in DOX-associated cardiomyopathy is conducted among various classes of chemical and pharmacological groups. Research Tasks: Development of methodological approaches for evaluation of cardioprotective activity of drugs in doxorubicin cardiomyopathy. Materials and Methods: Simulation of the cardiomyopathy was performed by intraperitoneal administration of DOX at a dose of 20 mg/kg 1 time per day. After 48 h, we assessed indices of a left ventricular contractility under conditions of high heart rate 480 bmp for 15 s on an isolated Langendorff heart of rats. As an additional index of the assessment of the cardioprotective action of pharmacological agents, StÐ¢Ð¢I coefficient was used, reflecting the diastole defect, which is an area under the curve of the buildup of an end diastolic pressure. To evaluate the myocardial damage, the isoenzyme creatine phosphokinase-MB and lactate dehydrogenase (LDH) in perfusate flowing from the isolated hearts were determined. For a comprehensive confirmation of the development of the simulated pathological processes, a morphological study of the hearts was performed. As drugs, enalaprilat (KRKA Slovenia) at the dose of 5 mg/kg intraperitoneally every 12 h, carvedilol (Teva, Israel) per os 1 time a day, and verapamil (JSC Alkaloid, Macedonia) at the dose of 5 mg/kg intraperitoneally 1 time a day were used. Results: In a control group with the DOX-induced cardiomyopathy under the conditions of submaximal stimulation frequencies (480 bpm), we observed the diastolic defect which numerically was StÐ¢Ð¢I = 8.3 Â± 0.3 c.u. which shows significant damage and the failure of the calcium pumps of cardiac myocytes. In an intact group, StÐ¢Ð¢I coefficient was 1.4 Â± 0.1 c.u. which is 8 times less than in the control group. The results of biochemical and morphological studies confirmed the degree of myocardial damage. In the comparative analysis of cardioprotective activity of drugs in doxorubicin cardiomyopathy, the studied compounds were located in the following sequence: Enalaprilat (5 mg/kg), carvedilol (30 mg/kg), verapamil (5 mg/kg). Conclusion: The fundamental difference in the area under the curve of the buildup of the end diastolic pressure under the conditions of submaximal stimulation frequencies (480 bpm) for 15 s in the intact group and the control group on the background of DOX administration naturally led to the necessity of introducing StÐ¢Ð¢I coefficient, which is quite revealing and informative. The obtained results allow to use StÐ¢Ð¢I at the screening of innovative molecules.